The Power of a Single Voice: the EU’s Contribution to Global Governance Architecture - Ana Postolache (Romanian Journal of European Affairs, 2012)
Over the past decades, global governance has become the most active phenomenon of world politics. From economics to politics, from climate change to international security, global governance became responsible for adjusting the international life in the name of the common good, relying on the power and the influence of the global key players. The aim of this paper is to assess the EU’s contribution to global governance architecture by analyzing the strengths of the EU approach with regard to global governance issues. Firstly, I will analyze the European Union ability to use its monolithic power and its key elements to influence the variables of global governance architecture. Put simply, the analysis looks at the internal governance system of the European Union and its analogue reflections for the global governance system. Secondly, I will limit my attention to three key areas of global governance, and I will adopt an analytical approach to identify and explore the EU practices with regard to: world trade, climate change and international security. In the end, I will discuss the EU performance power to act with a single voice on the entire spectrum of global governance.